2011
DOI: 10.3923/pjbs.2011.572.577
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ketamine and Fentanyl for Postoperative Pain Relief in Children Following Adenotonsillectomy

Abstract: Adenotonsillectomy has a high incidence of postoperative pain. Therefore, the purpose of this study was to evaluate the effectiveness and safety of either ketamine or fentanyl for postoperative pain relief in children following adenotonsillectomy. Sixty children aged 3-12 years, scheduled for adenotonsillectomy, were enrolled in this randomized, double-blind study. Patients were divided into two groups of 30 cases and received intravenous ketamine (0.5 mg kg(-1)) or fentanyl (1 microg kg(-1)). Modified Hannall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…164 • Local wound infiltration by the surgeon of a long-acting local anesthetic. 60,139,[165][166][167][168][169] • Intravenous fentanyl or morphine or other suitable agent (if available) to treat breakthrough pain in the PACU 51,[170][171][172] • Oral NSAIDs and/or paracetamol in adequate dosage during the entire postoperative period from the moment when the oral intake will be possible. 173,174 • Intravenous or oral tramadol or other suitable agent if available as rescue in the ward.…”
Section: Intraoperative Postoperativementioning
confidence: 99%
“…164 • Local wound infiltration by the surgeon of a long-acting local anesthetic. 60,139,[165][166][167][168][169] • Intravenous fentanyl or morphine or other suitable agent (if available) to treat breakthrough pain in the PACU 51,[170][171][172] • Oral NSAIDs and/or paracetamol in adequate dosage during the entire postoperative period from the moment when the oral intake will be possible. 173,174 • Intravenous or oral tramadol or other suitable agent if available as rescue in the ward.…”
Section: Intraoperative Postoperativementioning
confidence: 99%
“…In a study by Mukherjee et al 13 the efficacy of intravenous fentanyl and morphine for perioperative analgesia in children undergoing adenotonsillectomy were similar and had comparable pain scores and requirement of rescue analgesia in the postoperative period. They observed that postoperative vomiting was less with those received fentanyl.…”
Section: Discussionmentioning
confidence: 98%
“…Outcomes analyzed were postoperative pain (pain scores after leaving the operation room) [2][5], [8][23], postoperative (24 hours) analgesic requirements (either doses or percentage of patient receiving postoperative opioids or nonopioids analgesics)[2][4], [8][10], [12][14], [16], [19], [20], [22][25], time to first analgesic administration (opioid or nonopioid analgesics administered with a defined pain intensity target)[3]–[5], [8][10], [12][14], [18], [22], [23], [26], time to first oral uptake [2], [5], [13], [14], postoperative nausea and vomiting (percentage of patients or dose of antiemetics) [2], [8], [9], [12]–[18], [24], [25] and the occurrence of psycho-mimetic manifestations including nightmares [9], [10], [18], sleep pattern change (percentage of patients) [9], [10], [12], [19], hallucinations (percentage of patients) [5], [8], [18], [19], [25] or sedation (sedation scores) [4], [5], [8], [9], [11], [15], [17], [24]. These outcomes were compared with preoperative ketamine ...…”
Section: Methodsmentioning
confidence: 99%